Advancements in Anode Materials for Cathodic Protection: Nanostructured Alloys, Surface Modifications, and Smart Monitoring - Yahaya, Madaniyyu Sulaiman; Nahar, Kapil; Kumar, Dinesh; Usman, Habib Muhammad; Gambo, Abdulhaq Saleh; Umar, Tijjani Aminu; Sulaiman, Mustapha (Universitas Ahmad Dahlan, 2024)
This review critically examines advancements in anode materials for cathodic protection systems, focusing on overcoming the limitations of traditional materials like magnesium, zinc, aluminum, graphite, lead-silver alloys, and high-silicon cast iron (HSCI). Conventional anode materials, though widely used, face issues such as rapid degradation, high maintenance costs, and environmental harm. Novel materials, including mixed metal oxides (MMO), advanced aluminum-based alloys, nanostructured materials, and conductive polymers, offer superior electrochemical properties, enhanced durability, and improved performance in aggressive environments like seawater. This review also highlights the role of surface modifications and coatings, such as platinum on titanium and ceramic coatings, in boosting corrosion resistance. Moreover, smart monitoring systems, integrated with IoT and SCADA technologies, are explored for their potential to improve the longevity and efficiency of cathodic protection systems. The paper emphasizes the urgent need for sustainable solutions due to the substantial economic and environmental costs of corrosion, particularly in high-risk industries like oil and gas, maritime, and infrastructure. Future research directions, including the development of hybrid systems combining coatings with CP technologies and the application of advanced alloys and nanostructured materials, are proposed to address the long-term performance and ecological impacts of CP systems.